Prejudicial Attitudes and Labor Market Outcomes. (11th April 2018) - Rode, Ashwin; Shukla, Anand J.
Abstract: We explore whether and to what extent differences in prejudicial attitudes can be associated with the variation in Black–White labor market gaps across US metropolitan areas. Prejudicial attitudes are quantified using novel data on racially charged Internet searches. We find that prejudicial attitudes matter for labor market outcomes, but only for workers who are not college graduates. For this group, a racially charged search rate that is one standard deviation higher is associated with a 17 per cent higher unexplained Black–White gap in annual income and 21 per cent higher unexplained hourly wage gap.